2019
DOI: 10.1177/2329488419868520
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Language Intensity: A Study of Wyoming Superintendents Motivating Language Use as Perceived by Their Principals

Abstract: The purpose of this study was to extend the field of motivating language theory (MLT) by providing a conceptual framework and methodology for determining low-ML and high-ML leader levels. This quantitative study, specifically, studied the Motivating Language of Wyoming K-12 superintendents operating in the role of CEOs as perceived by their principals. The results of this study found that Wyoming Superintendents with high-ML levels positively influencing employee outcomes in the areas of communication satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…Literature has consistently shown that ML is positively related to a wide array of employee and organizational outcomes, including job performance (Holmes, 2012; J. Mayfield & Mayfield, 2010), job satisfaction (Sharbrough et al, 2006; Simmons & Sharbrough, 2013), job creativity and innovation (Sexton, 2013; Wang et al, 2009), organizational commitment (Krause, 2013; Madlock & Sexton, 2015), and intention to stay (Krause, 2013; J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature has consistently shown that ML is positively related to a wide array of employee and organizational outcomes, including job performance (Holmes, 2012; J. Mayfield & Mayfield, 2010), job satisfaction (Sharbrough et al, 2006; Simmons & Sharbrough, 2013), job creativity and innovation (Sexton, 2013; Wang et al, 2009), organizational commitment (Krause, 2013; Madlock & Sexton, 2015), and intention to stay (Krause, 2013; J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Motivating language theory research shows that communicating support for a follower’s emotions has a positive influence on follower outcomes (Gutierrez-Wirsching et al, 2015; M. Mayfield & Mayfield, 2009) in a wide variety of settings (Holmes, 2012; Holmes & Parker, 2017; Luca & Gray, 2004; Madlock & Sexton, 2015; Sharbrough, Simmons, & Cantrill, 2006). However, empathetic leadership goes beyond this research stream and focuses on how leaders empathetic support influences follower performance.…”
Section: Empathetic Leadership Workplace Outcomes and Causal Mechanmentioning
confidence: 99%
“…(2) Superintendent talk is the medium of superintendent practice through the intentional and strategical linkage of words and actions to maximize the impact of leadership practice, known as motivating language (ML) (Holmes, 2021;Holmes and Parker, 2019).…”
mentioning
confidence: 99%
“…(3) Whether at the employee level or the organizational level, outcomes are impacted by the degree of effectiveness of a superintendent's talk, which is a measure of ML ability and intensity (Holmes and Parker, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation